How did the public respond to the 2015 expert consensus public health guidance statement on workplace sedentary behaviour? A qualitative analysis - Benjamin Gardner; Lee Smith; Louise Mansfield (BMC, 2017)
Abstract Background In June 2015, an expert consensus guidance statement was published recommending that office workers accumulate 2-4 h of standing and light activity daily and take regular breaks from prolonged sitting. This paper describes public responses to media coverage of the guidance, so as to understand public acceptability of the recommendations within the guidance, and perceptions of sitting and standing as health behaviours. Methods UK news media websites that had reported on the sedentary workplace guidance statement, and permitted viewers to post comments responding to the story, were identified. 493 public comments, posted in a one-month period to one of six eligible news media websites, were thematically analysed. Results Three themes were extracted: (1) challenges to the credibility of the sedentary workplace guidance; (2) challenges to the credibility of public health; and (3) the guidance as a spur to knowledge exchange. Challenges were made to the novelty of the guidance, the credibility of its authors, the strength of its evidence base, and its applicability to UK workplaces. Public health was commonly mistrusted and viewed as a tool for controlling the public, to serve a paternalistic agenda set by a conspiracy of stakeholders with hidden non-health interests. Knowledge exchanges focused on correcting others' misinterpretations, raising awareness of historical or scientific context, debating current workplace health policies, and sharing experiences around sitting and standing. Conclusions The guidance provoked exchanges of health-promoting ideas among some, thus demonstrating the potential for sitting reduction messages to be translated into everyday contexts by lay champions. However, findings also demonstrated confusion, misunderstanding and misapprehension among some respondents about the health value of sitting and standing. Predominantly unfavourable, mistrusting responses reveal significant hostility towards efforts to displace workplace sitting with standing, and towards public health science more broadly. Concerns about the credibility and purpose of public health testify to the importance of public engagement in public health guidance development.